2016
DOI: 10.1007/s00262-016-1880-z
|View full text |Cite
|
Sign up to set email alerts
|

Topical treatment of melanoma metastases with imiquimod, plus administration of a cancer vaccine, promotes immune signatures in the metastases

Abstract: Introduction Infiltration of cancers by T-cells is associated with improved patient survival and response to immune therapies; however, optimal approaches to induce T-cell infiltration of tumors are not known. This study was designed to assess whether topical treatment of melanoma metastases with the TLR7 agonist imiquimod plus administration of a multipeptide cancer vaccine will improve immune cell infiltration of melanoma metastases. Patients and Methods Eligible patients were immunized with a vaccine comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
(40 reference statements)
0
30
0
Order By: Relevance
“…In a previous study, no difference was found in the numbers of pretreatment vHSILinfiltrating CD4 + and CD8 + T cells between patients with or without a complete clinical response after vaccination with an HPV16-E6E7L2 fusion protein vaccine. 29 This can be explained by the fact that these patients were pretreated with imiquimod, 29 which is known to induce strong local inflammation 30 that is reflected by infiltration with CD4 + and CD8 + T cells, activated DCs and macrophages, 31 thereby recreating the desired immune microenvironment. But also because no functional assessment of the infiltrating T cells was performed, while our data clearly point at the role of CD4 + Tbet + (type 1) Th cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, no difference was found in the numbers of pretreatment vHSILinfiltrating CD4 + and CD8 + T cells between patients with or without a complete clinical response after vaccination with an HPV16-E6E7L2 fusion protein vaccine. 29 This can be explained by the fact that these patients were pretreated with imiquimod, 29 which is known to induce strong local inflammation 30 that is reflected by infiltration with CD4 + and CD8 + T cells, activated DCs and macrophages, 31 thereby recreating the desired immune microenvironment. But also because no functional assessment of the infiltrating T cells was performed, while our data clearly point at the role of CD4 + Tbet + (type 1) Th cells.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, imiquimod is being tested (1) in combination with neoadjuvant sonidegib followed by surgery or imiquimod for the treatment of basal cell carcinoma (NCT03534947); (2) in combination with curettage surgery as compared to surgery alone in patients with basal cell carcinoma (NCT02242929); (3) in combination with 5-fluorouracil for the treatment of squamous cell carcinoma (NCT03370406); (4) in combination with pembrolizumab, an FDA-approved immune checkpoint blocker specific for PD-1, 169 in patients with melanoma 157 (NCT03276832); (5) compared to 5-flurouracil-based e1526250-4 chemotherapy or observation for the treatment of anal carcinoma (NCT02059499); (6) as a standalone immunotherapeutic agent or following large loop excision of the transformation zone (LLETZ) in patients with cervical intraepithelial neoplasms (CINs) (NCT02917746); (7) in combination with a DNA-based vaccine, GX-188E 170 (NCT03206138); (8) in combination with 5-flurouracil for the treatment of patients with high-grade cervical intraepithelial neoplasia (NCT03196180); (9) in combination with conization of the uterine cervix based on loop electrosurgical excision procedure (LEEP) as compared to LEEP alone for patients with CIN (NCT03233412); (10) as standalone therapy or in combination with a nonavalent HPVspecific vaccine for patients with CINs (NCT02864147); (11) as a single agent compared to LLETZ for patients with CINs (NCT02669459); (12) in combination with a DNA vaccine, VGX-3100, [171][172][173][174] for patients with HPV-16 and/or HPV-18related high grade squamous intraepithelial lesion (HSIL) of the vulva (NCT03180684); (13) in combination with doxycycline for the treatment of cutaneous T cell lymphoma (NCT03116659); (14) in combination with a peptide vaccine, iVAC-L-CLL01, 175,176 and the immunomodulatory agent lenalidomide [177][178][179][180] in patients with chronic lymphocytic lymphoma (NCT02802943); (15) combined with a DRibble-based vaccine 181 and DC-activated cytokine-induced killer (DC/CIK) cells and GM-CSF in NSCLC patients (NCT03057340); (16) as adjuvant therapy for patients with anal HPV lesions (NCT03289260); and (17) in combination with DPV-001, another DRibble-based vaccine, 107,[182][183][184] in patients with advanced prostate carcinoma (NCT02234921). BCG is being investigated in clinical settings: (1) in combination with rapamycin 185 for bladder carcinoma ...…”
Section: Recently Initiated Clinical Trialsmentioning
confidence: 99%
“…Peptide-based vaccination was employed as a standalone adjuvanted intervention, 140-146 or combined with chemotherapy 147-149 radiation therapy 147,150 or other forms of treatment including other immunotherapies. 148,149,151-158 These studies enrolled patients with hematological malignancies, 151,159 brain tumors, 152,153 non-small cell lung carcinoma (NSCLC), 140,147,160 breast cancer, 141,148,161 , prostate carcinoma, 142,154 melanoma, 144-146,155-158,162 . ovarian cancer.…”
Section: Literature Updatementioning
confidence: 99%
“…Mild side effects were sporadic and included flu-like symptoms, fatigue and minor reactions at the injection site. Immunes responses driven by vaccination were documented in a variety of studies based on (1) interferon gamma (IFNG) production by T cells with enzyme-linked immunospot (ELISPOT) assays, 142,151,152,154,155 (2) tumor infiltration by CD4 + and CD8 + lymphocyte infiltration, 144,145,147,157,158 or (3) presence of peptide-specific antibodies in the serum. 158 Sporadic clinical responses were also documented (see below).…”
Section: Literature Updatementioning
confidence: 99%